Study of congenital heart diseases in neonates - Amroliwala, Rakesh; Rasania, Manish; Memon, Raish; Pokharna, Avina; Shah, Dixa (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital heart disease defined as an abnormality in cardio circulatory structure or function that is mostly present at birth; even it is discovered much later. Recognition of congenital heart disease in newborn is important as this group abnormality constitutes a significant proportion of congenital malformation that present in the neonatal life, and their early detection is important for appropriate management and good outcome. Objectives of present study were to evaluate clinical profile and outcome of various CHDs identified during neonatal period and to study effect of paracetamol used for pharmacological closure of PDA in preterm neonates. Methods: The study was conducted prospectively in NICU, Dhiraj hospital, Department of Pediatrics and Neonatology from January 2016 to June 2017 (1.5 years span). Echocardiography screening of all neonates suspected of having CHD was done. Details of all neonates having CHD diagnosed by echocardiography were noted in the prescribed Performa and their incidence, clinical profile and outcome was studied. Results: Total 69 cases of CHD diagnosed by Echocardiography in neonatal period were studied. Incidence of CHD among neonates born at Dhiraj hospital was 8.48 per 1000 live birth. Male: female ratio of all CHD cases was 1.38:1. Risk of neonate with CHD is highest (18.18%) in extremely low birth weight neonates. Incidence of CHD was 4.08% in preterm < 34 weeks, 3.47% in late preterms and 0.51% in full term neonates. 86.95% were diagnosed within first week of life. 26.09% babies had associated anomalies. Presenting problem of neonates was breathing difficulty 42 (60.87%), feeding difficulty 36 (52.17%) and cyanosis 5 (7.25%). 8 (11.59%) neonates were asymptomatic. The most common presenting sign was murmur 46 (75.71%). 56 (81.16%) had Acyanotic CHD and 13 (18.84%) had Cyanotic CHD. Amongst 56 (81.16%) Acyanotic CHD cases, commonest was PDA in 44 (78.5%), followed by VSD in 18 (32.14%), ASD in 5 (12.5%) either in isolation or in combination with other lesions. Amongst Cyanotic Congenital Heart Disease, maximum incidence was of Tricuspid Atresia (TA) in 4 (30.76%) cases; followed by TGA in 3 (23.07%). 20 preterm neonates with PDA received paracetamol for PDA closure. 9 (45.0%) responded to paracetamol while 11 (55%) did not respond. 47(68.12%) were discharged, 10(14.49%) went left against medical advice, 7(10.14%) were referred to higher centre for surgery and 5(7.25%) babies expired. Conclusions: Early recognition of congenital heart disease during neonatal life is important as its appropriate and timely management can result in good outcome.